Effects of weblogging in English on ESL students' writing apprehension at Universiti Teknologi MARA, Sabah / Suzie Wong @ Suzie Rahman - Rahman, Suzie (Penerbit UiTM (UiTM Press), 2015)
The affordances of technological advances such as the Internet have changed the way writing is taught and learnt. It undeniably impacts the cognitive and affective states in writing which include one's writing apprehension. Students, who are still in the process of acquiring English as a second language (ESL), commonly experience writing apprehension when writing in English. Thus, this study aims to describe the effects of using the weblog as a medium for essay writing in relation to writing apprehension among ESL students undergoing an Intermediate English course at Universiti Teknologi MARA, Sabah. The quantitative research approach employing the Quasi-experimental design was used in this study. One hundred fifty-five diploma students participated in the experiment with 79 and 76 participants in each of the respective Experimental group and Control group. Writing through blogging was used with the Experimental group, while writing through non-blogging pen-paper method was used with the Control group. Both groups were pre-tested and post-tested with an adapted Second Language Writing Anxiety Inventory (SLWAI) questionnaire.